ChemInform Abstract: Acid‐Catalyzed Ring‐Opening Cyclization of Spirocyclopropanes for the Construction of a 2‐Arylbenzofuran Skeleton: Total Synthesis of Cuspidan B. Issue 45 (October 2016) - Nambu, Hisanori; Ono, Naoki; Yakura, Takayuki
Abstract: The utility of this method is demonstrated in the first total synthesis of cuspidan B (V).